Distribution and characteristics of slow‐cycling cells in rat vocal folds. (4th February 2016) - Kawai, Yoshitaka; Kishimoto, Yo; Suzuki, Ryo; Tsuji, Takuya; Hiwatashi, Nao; Tateya, Ichiro; Yamamoto, Norio; Nakamura, Tatsuo; Kanemaru, Sin‐ichi; Hirano, Shigeru
Abstract : Objectives/Hypothesis: Stem cells are known to proliferate at a slow rate in adult organs, and thus slow‐cycling cells exhibiting pluripotency are considered tissue‐specific stem cells in some organs. Slow‐cycling cells in the vocal fold (VF) have not been well documented. Here we sought to clarify the distributions and characteristics of slow‐cycling cells in rat VFs. Methods: We applied double‐labeling technique to detect the distribution of slow‐cycling cells. We injected the exogenous proliferation marker 5‐bromo‐2'‐deoxyuridine (BrdU) into Sprague‐Dawley rats. After a chasing period, VFs were immunostained with antibodies to BrdU and the second endogenous proliferation marker, Ki‐67. BrdU (+) Ki‐67(+) cells were regarded as slow‐cycling cells and counted by VF regions. To reveal slow‐cycling cells' characteristic, their immunophenotypes were histologically investigated and their kinetics in injured VFs were evaluated. Results: Most slow‐cycling cells were detected in the basal layer of the epithelium. Slow‐cycling cells in the epithelium displayed a low positive ratio of E‐cadherin and CK5 and a high positive ratio of vimentin and CD31 as compared with the other epithelial cells. The expression of S100A4 was low in slow‐cycling cells of the lamina propria and the macula flava. FGFR1, HAS1, HAS2, and HAS3 were not detected in the slow‐cycling cells. A time‐dependent reduction of slow‐cycling cells was observed in injured VFs. Conclusion: Most slow‐cycling cells resided in the epithelium, exhibiting various phenotypes in a relatively undifferentiated condition, and they are suspected to contribute to the tissue repair of the injured VFs. Level of Evidence: N/A. Laryngoscope, 126:E164–E170, 2016